Intestinal Bacteria as Powerful Trapping Lifeforms for the Elimination of Radioactive Cesium - Saito, Kazuki; Kuroda, Kengo; Suzuki, Rie; Kino, Yasushi; Sekine, Tsutomu; Shinoda, Hisashi; Yamashiro, Hideaki; Fukuda, Tomokazu; Kobayashi, Jin; Abe, Yasuyuki; Nishimura, Junko; Urushihara, Yusuke; et al. (Frontiers in Veterinary Science, 2019)
In March 2011, the accident at the Fukushima Daiichi Nuclear Power Plant caused diffuse radionuclides such as Cesium (Cs)-137 to enter the environment. Ever since this accident, Cs-137 contamination in foods has become a serious problem. In this study, we determined the concentrations of Cs-137 in the feces, urine, and ruminal contents of cattle, and demonstrated the possibility of the powerful elimination from the body by intestinal bacteria. The results revealed a high Cs-137 concentration in the feces, and it was even higher than that in skeletal muscle and other samples in several animals. Furthermore, intestinal bacteria were able to trap Cs-137, showing an uptake ratio range of 38–81% in vitro. This uptake appeared to be mediated through the sodium ion–potassium ion pump in the bacterial cell membrane, because the uptake ratio of Cs-137 was decreased in medium with a high potassium concentration. In addition, it was demonstrated that intestinal bacteria hindered the trapping of Cs-137 by the animal. Cattle’s feces showed high concentration of Cs-137 and intestinal bacteria trapped Cs-137. This study is the first report showing that intestinal bacteria contribute to the elimination of Cs-137 from the body.